Relationship of pain and fatigue with health-related quality of life and work in patients with psoriatic arthritis on TNFi: results of a multi-national real-world study. Issue 2 (1st July 2020) - Conaghan, P G; Alten, Rieke; Deodhar, Atul; Sullivan, Emma; Blackburn, Stuart; Tian, Haijun; Gandhi, Kunal; Jugl, Steffen M; Strand, Vibeke
Abstract : Background/Objective: The incidence of pain and/or fatigue in people with psoriatic arthritis (PsA) is associated with reduced health-related quality of life (HRQoL) and the ability to work, despite modern advanced therapeutic approaches. This real-world, international study examined these relationships in patients with PsA treated with tumour necrosis factor inhibitors (TNFi). Methods: Data from 13 countries were analysed. Patients with PsA and their physicians completed questionnaires capturing demographics, current therapy, current disease status, HRQoL and work status via Medical Outcomes Study 36-Item Short-Form version 2 (SF-36v2), 3-level 5-dimension EuroQoL questionnaire, Health Assessment Questionnaire Disability Index, and Work Productivity and Activity Impairment (WPAI) questionnaire. Results: 640 patients with PsA were included who had been receiving TNFi for ≥3 months and had completed SF-36v2 bodily pain and vitality domains. Of these, 33.1%, 29.2% and 37.7% of patients reported no, moderate and severe pain, respectively, and 31.9%, 22.5% and 45.6% of patients reported low, moderate and severe fatigue, respectively. Scores across HRQoL variables and WPAI were significantly different across pain and fatigue cohorts (all p<0.0001), with HRQoL and WPAI measures considerably worse in patients with moderate to severe pain or fatigue than those with low pain or fatigue. Conclusions: Despite treatment with biologic agents such as TNFi, data from this global study demonstrated that substantial pain and/or fatigue persist in patients with PsA and that these are significantly associated with reduced HRQoL, physical function and work productivity. These findings suggest that there is an unmet need for additional PsA therapies.